Speech by the Hon’ble the Chief Minister at the Annual General Meeting of the Central Welfare Council Malaya Penang State Branch, 29th April, 1970 at 5.00 p.m. at the Civics Centre, Farquhar Street, Penang. - Lim, Chong Eu (1970)
Mr.Chairman and Members of the Committee,I wish to thank your Chairman an d members for inviting me once again to address you on the occasion of the Fourth Annual General Meeting of your Council.